MRI Predictors of Failure in Non-operative Management of Ulnar Collateral Ligament Injuries in Professional Baseball Pitchers - Lynch, Thomas Sean (Orthop J Sports Med, 2016)
OBJECTIVES: Ulnar collateral injuries (UCL) of the elbow are prevalent among professional baseball pitchers. The decision on initial operative versus nonoperative management of these injuries remains subjective in many cases, with reported success rates with nonoperative management ranging from 42 to 93% in professional throwing athletes. No studies to date have identified objective characteristics specific to success or failure of nonoperative intervention. The purpose of this study was to identify radiologic predictors for success or failure in nonoperative management of ulnar collateral ligament injuries in professional pitchers. METHODS: A retrospective review of pitchers sustaining UCL injuries between 2006 and 2015 from one professional baseball organization (one major league team and all minor league teams included) was performed. UCL injuries were identified in 38 players based on clinical and radiographic findings. Six players underwent initial surgical intervention without attempted nonoperative intervention and were excluded from analysis. This left 32 (84%) professional pitchers who underwent an initial trail of nonoperative treatment for partial UCL tears. Success was defined as return to same level of play (RTSP) or higher for >1 year. Failure was defined as recurrent pain or weakness requiring surgical intervention after a minimum of 3 months’ rest when attempting a return to throw rehabilitation program. MRI findings were classified as high or low grade sprains, proximal or distal location of injury, and with or without the presence of concomitant chronic findings. RESULTS: Of the 32 patients who underwent nonoperative management, 10 (36%) failed and required subsequent ligament reconstruction. Between the success and failure groups, there was no significant difference seen in total shoulder arc of motion (P=.7776), shoulder internal rotation deficit (P=.3846) or loss in elbow extension (P=.0644) at the time of injury. When comparing MRI findings between the groups, distal tears were found in 90% (9/10) of those who failed nonoperative management compared to 18.2% (4/22) who were successful nonoperatively (P=<.0001). No significant difference was seen with high grade tears (P=.0817) between the groups. When adjusting for age, location and evidence of chronic changes on MRI, the likelihood of failing nonoperative management was 22.7 times greater (P=.001) with distal tears. No other variable reached significance, and no combination of variables showed a greater likelihood than distal location alone. CONCLUSION: In professional pitchers, distal ulnar collateral ligament tears described on MRI show significantly higher rates of failure with nonoperative management compared to proximal tears. This information provides an objective measure for evaluating operative versus nonoperative management of ulnar collateral ligament injuries in throwing athletes.